问题 解答题

已知an-bm≠0,a≠0,ax2+bx+c=0,mx2+nx+p=0,求证:(cm-ap)2=(bp-cn)(an-bm).

答案

证明:∵an-bm≠0

∴方程ax2+bx+c=0和方程mx2+nx+p=0有相等的根.

方程ax2+bx+c=0可化为x2+

b
a
x+
c
a
=0   ①

方程mx2+nx+p=0可化为x2+

n
m
x+
p
m
=0   ②

把方程①-②可得:(

b
a
-
n
m
)x+(
c
a
-
p
m
)=0

解方程得:

bm-an
am
x+
cm-ap
am
=0

(bm-an)x+(cm-ap)=0

x=

ap-cm
bm-an

把x=

ap-cm
bm-an
代入方程ax2+bx+c=0

得:a(

ap-cm
bm-an
)2+b(
ap-cm
bm-an
)+c=0

a(ap-cm)2+b(ap-cm)(bm-an)+c(bm-an)2=0

a(ap-cm)2+(bm-an)(abp-bcm+bcm-can)=0

a(ap-cm)2+a(bm-an)(bp-cn)=0

∵a≠0,

∴两边同时除以a得到:(ap-cm)2+(bm-an)(bp-cn)=0

故(ap-cm)2=(bp-cn)(an-bm).

解答题
判断题